Eloy Alfaro Cadavid Macias: the alter ego Hebert Castro - Medina Pérez, Gonzalo (Folios, revista de la Facultad de Comunicaciones y Filología, 2012)
Through the work of Antioquian radio script-writer Eloy Alfaro Cadavid Macias, a Colombian radio protagonist of the fifties, we enter not only into the evolution and development of this media but we also ventured into the history of violence in our country. It is impossible to address Colombian political issues, especially in certain periods marked by armed conflict, without analytically looking back to the role played by this media, given the influence that it has exercised. In addition to engaging some conceptualizations of humor, the text reveals the course of Cadavid Macias in dramatized radio and, specifically, his happy and final meeting with the Uruguayan humorist Hebert Aaron Castro, who created a landmark in its genre and in the different radio stations in which he was leading artist. The characters represented by Hebert Castro, directly or indirectly, came from the inspiration of Cadavid Macias who in turn funneled humorous experiences engendered in other countries, especially Argentina. The end point of this article focuses on trying to establish a comparison between the humor created by Cadavid Macias and represented by Hebert Castro, and which in recent years, in our radio, receives the me denomination. In short, returning to Colombian radio recent past will serve to discern the intended humorous production now taking place in our country.